Novel lumen‐apposing metal stent for the drainage of pancreatic fluid collections: An Italian multicentre experience. Issue 9 (1st November 2018) - Petrone, Maria Chiara; Archibugi, Livia; Forti, Edoardo; Conigliaro, Rita; Di Mitri, Roberto; Tarantino, Ilaria; Fabbri, Carlo; Larghi, Alberto; Testoni, Sabrina Gloria Giulia; Mutignani, Massimiliano; Arcidiacono, Paolo Giorgio
Abstract : Background: Endoscopic ultrasound (EUS)‐guided drainage is the procedure of choice for pancreatic fluid collection (PFC) management. Recently developed lumen‐apposing fully covered self‐expandable metal stents (LAMSs) may facilitate drainage, especially of necrotic and complex PFCs. Objective: To evaluate the feasibility and efficacy of a newly developed LAMS (Nagi, Taiwong Medical Co. Ltd, South Korea) in the drainage of PFCs. Methods: Retrospective analysis of LAMS drainage of PFCs from seven centres. Patient demographic, EUS and radiological findings, PFCs aetiology, procedural technical and clinical success, and adverse events were evaluated. Results: Sixty‐seven patients with mean age 58.8 ± 14 years (68.7% males) were included in the analysis. Of these, 44 patients had pseudocyst (PP) and 23 patients had walled‐off pancreatic necrosis (WOPN). Technical success was achieved in 98.5% of cases and clinical success in 94%. The adverse event rate was 24.2%, higher and mostly due to stent migration and occlusion in the WOPN group as compared to the PP group, despite the time to stent removal being significantly lower in the WOPN group. Conclusions: PFC drainage using the Nagi stent is highly feasible and effective, with a relatively safe profile. Future studies enrolling more patients with complex PFCs are needed to clearly establish the role of this stent in PFC management.